Asymptomatic Versus Symptomatic Ankle Joints in Rheumatoid Arthritis: A High‐Resolution B‐Mode and Power Doppler Ultrasound Study. Issue 6 (26th May 2016) - Alsuwaidi, Mohammed; Ehrenstein, Boris; Fleck, Martin; Hartung, Wolfgang
Abstract : Objective: Ankle joints are frequently neglected in activity scoring systems, including the Disease Activity Score in 28 joints (DAS28). Only a few studies have assessed pathologies detected by ultrasonography of the ankles in symptomatic rheumatoid arthritis (RA) patients. We evaluated ankle joints in RA patients regardless of symptomatology, using musculoskeletal ultrasound (MSUS) as well as power Doppler ultrasound (PDUS). Methods: A total of 160 ankle joints of 80 RA patients were examined using MSUS and PDUS, according to the European League Against Rheumatism MSUS guidelines. Additionally, the talonavicular joints (TNJs) and the medial and the lateral tendon compartments were examined. The visual analog scale (VAS) score was recorded for each patient. Results: A total of 80 RA patients with a median age of 60 years and disease duration of 5 years were enrolled in our study. The median DAS28 score was 5. A total of 97 ankles were painful (VAS 1–10), whereas 63 ankles were asymptomatic (VAS 0). Overall, the predominant pathology was arthritis of the tibiotalar joint (TTJ) and/or TNJ in 124 ankles (77%), followed by tenosynovitis of the medial compartment tendons in 44 ankles (28%). Arthritis of the TTJ was present in 59% and synovitis of the TNJ in 35% of the symptomatic ankles. In asymptomatic ankles, TTJ synovitis was detected in 35%, whereas TNJ arthritis was observed in 18%. PDUS activity was higher in the subgroup of symptomatic ankles. Conclusion: The most frequent pathologies detected by MSUS were arthritis of the TTJ and TNJ, followed by tenosynovitis of the medial compartment tendons. Pathologic findings were more frequent in symptomatic but also common in asymptomatic patients, whereas PDUS activity was generally low and mainly observed in symptomatic patients.